Development of carbon-based metal free electrochemical sensor for hydrogen peroxide by surface modification of carbon nanowalls. (30th August 2022) - Bohlooli, Fatemeh; Anagri, Abdessadk; Mori, Shinsuke
Abstract: A novel metal-free amperometric sensor based on O2 /Ar plasma modified carbon nanowalls (CNW) was successfully developed for non-enzymatic detection of hydrogen peroxide (H2 O2 ). This study demonstrates the effectiveness of surface modification of CNW by O2 /Ar plasma treatment to improve the electrochemical sensing performance. It was shown that the CNW treated in low oxygen flow rate (O2 /Ar: 0.1/10sccm) exhibited the highest concentration of incorporated oxygen on its structure, which consequently resulted in conversion of intrinsic hydrophobicity of CNW to hydrophilicity. Interestingly, however, further increase in oxygen flow rate did not increase the oxygen content of CNW structure, but instead it resulted in an increment in the defect and contributing less oxygen on CNW surface. The highest amperometric response was observed for the CNW treated with O2 /Ar: 1.0/10sccm, which has lower oxygen content than the CNW treated with O2 /Ar: 0.1/10sccm, but still possessing hydrophilic characteristic as well as owning more defect sites. These results can suggest the importance of both defects and oxygen-containing functional groups in electrochemical behavior of the electrode as both defects and oxygen-containing functional groups can act as potential active sites for electrochemical reactions and oxygen-containing functional groups can enhance the hydrophilicity and surface area wetted by the electrolyte. The modified CNW exhibited the potential for quantification analysis of H2 O2 with a wide linear range covering from 50 μM to 28000 μM, a good sensitivity of 126.6 μA/mM.cm 2 and a detection limit of 0.91 μM (S/N = 3). This study demonstrates the success in utilizing the CNW structure towards detecting of H2 O2 as a metal-free sensor. Graphical abstract: Image 1